A textile-based triboelectric nanogenerator with humidity-resistant output characteristic and its applications in self-powered healthcare sensors. (August 2018) - Jao, Yun-Ting; Yang, Po-Kang; Chiu, Che-Min; Lin, Yu-Jhen; Chen, Shuo-Wen; Choi, Dongwhi; Lin, Zong-Hong
Abstract: Functional textiles have evoked great attention due to their promising applications in next-generation wearable and biomedical electronics. However, the constraints on the harsh operation environment and ineffective response to instantly reflect the physical status remain critical challenges. Herein, we develop a chitosan-based triboelectric nanogenerator (C-TENG) to harvest biomechanical energy from human motions, in which a nanostructured chitosan-glycerol film is utilized to promote the commercial textile into a multi-functional textile based on its transparency, flexibility, biocompatibility and adaptability to commercial fabrics. The output characteristics of the as-fabricated C-TENG are notably stable under various humidity conditions, distinguishing them from conventional TENGs. As the relative humidity (RH) changes from 20% to 80%, the electric output of the C-TENG remains unchanged, in contrast to the performance degradation observed for conventional TENGs. Moreover, the C-TENG can be further developed into various kinds of self-powered healthcare sensors for humidity, sweat, and gait phase detection. More importantly, the designed humidity sensor based on the C-TENG exhibits a promising advancement in sensitivity compared with conventional TENG-based humidity sensors. This work presents a new step in applying multi-functional textiles to wearable energy harvesters and self-powered sensors, which have high potential for future smart clothing products and personalized healthcare sensors. Graphical abstract: A textile-based and humidity-resistant triboelectric nanogenerator (C-TENG) is successfully demonstrated, which can be further developed into self-powered healthcare sensors, such as humidity, sweat, and gait phase sensing. fx1 Highlights: The concept of the self-powered healthcare systems are successfully demonstrated in this paper. Diverse applications of the self-powered healthcare systems are realized, including humidity, sweat and gait phase sensing. The humidity-resistant output characteristics are successfully achieved in chitosan-based triboelectric nanogenerator.